2001
DOI: 10.1148/radiographics.21.1.g01ja10121
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Clinical and Radiographic Findings in Pediatric Mycoplasma Pneumonia

Abstract: Clinical symptoms in mycoplasma infection are nonspecific. Pulmonary involvement may be widespread or focal and segmental and is accompanied by signs including rales, rhonchi, and decreased breath sounds. Although manifestations of mycoplasma infection are usually confined to the respiratory tract, a wide variety of extrarespiratory manifestations can also occur, including more severe associated diseases such as myocarditis, acute disseminated encephalomyelitis, and cerebral arteriovenous occlusion. The radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
1
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 12 publications
2
69
1
6
Order By: Relevance
“…In this case, cough and fever are the most-frequent symptoms; they are inconstantly associated with wheezing, dyspnoea, and bilateral rattles. Chest X-rays show nonspecific bilateral infiltrates and bronchial thickness, and biological inflammation markers may be lacking [30]. In fact, radiological findings of pneumonia by M. pneumoniae are highly varied.…”
Section: Pulmonary Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, cough and fever are the most-frequent symptoms; they are inconstantly associated with wheezing, dyspnoea, and bilateral rattles. Chest X-rays show nonspecific bilateral infiltrates and bronchial thickness, and biological inflammation markers may be lacking [30]. In fact, radiological findings of pneumonia by M. pneumoniae are highly varied.…”
Section: Pulmonary Manifestationsmentioning
confidence: 99%
“…Lobar (generally unilateral) condensation, bronchopneumonic shadows, reticular and reticulonodular infiltrates can be observed [31]. John et al [30] prospectively assessed the radiological features of 42 children with M. pneumoniae pneumonia. They reported focal reticulonodular infiltrates in a single lobe in 52% of cases and they found that the lower lobes were more affected than the upper lobes.…”
Section: Pulmonary Manifestationsmentioning
confidence: 99%
“…They also emphasized that the imaging findings of their case suggest a differential diagnosis of atypical infections (viral infections, Mycoplasma, Chlamydia, or Legionella infections), septic emboli, ARDS, cryptogenic organizing pneumonia, eozinophylic pneumonitis and hypersensitivity pneumonitis. Moreover, they observed that the CT findings of the patient was different from hydrostatic or cardiogenic pulmonary odema, which usually shows a perihilar distribution of confluent GGO associated with pleural effusion (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…PPE due to M. pneumoniae has been reported in 4-20% of patients with CAP. Although PPE is generally small, unilateral and does not require chest tube insertion, it can be massive and bilateral 1,[21][22][23][24][25] . In a retrospective observational study involving 121 hospitalized children and adolescent patients with CAP/ PPE, M. pneumoniae without co-infection was detected in 34 and M. pneumoniae/S.…”
Section: Discussionmentioning
confidence: 99%